2004
DOI: 10.1081/hem-200037724
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Rapid Determination of βS‐Globin Haplotypes: Sequencing of theAγ‐IVS‐II Region

Abstract: beta-Globin gene cluster haplotypes were originally determined by restriction endonuclease mapping with Southern blots of polymorphic sites around the gene cluster. Over the years, haplotyping has been found to be useful, not only in population genetics but also in predicting the severity of hemoglobinopathies such as sickle cell disease. The sickle mutation occurs on five distinct haplotypes. The hitherto used methods are cumbersome and time-consuming, making haplotype determination a tedious procedure. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…[1][2][3] Previously it was reported that a unique repetitive sequence at the A gene IVS-II of the -S globin chain can discriminate African haplotypes of Hb S. These reports analyzed the haplotypes and gave the sequences as follows: Benin (TG)10CGCGCGCG(TG)7TC; Bantu (TG)10(CG)3(TG)9TC; Senegal (TG)13TC; Arab-India (TG)13TC and Cameroon (TG)12(CG)3(TG)7TC. 4,5 We aimed to sequence the A gene IVS-II region of the globin gene for hemoglobin S and other common hemoglobin variants in Turkish population.…”
Section: A Gene Repeats Polymorphism For the Analysis Of Haplotypes Omentioning
confidence: 99%
“…[1][2][3] Previously it was reported that a unique repetitive sequence at the A gene IVS-II of the -S globin chain can discriminate African haplotypes of Hb S. These reports analyzed the haplotypes and gave the sequences as follows: Benin (TG)10CGCGCGCG(TG)7TC; Bantu (TG)10(CG)3(TG)9TC; Senegal (TG)13TC; Arab-India (TG)13TC and Cameroon (TG)12(CG)3(TG)7TC. 4,5 We aimed to sequence the A gene IVS-II region of the globin gene for hemoglobin S and other common hemoglobin variants in Turkish population.…”
Section: A Gene Repeats Polymorphism For the Analysis Of Haplotypes Omentioning
confidence: 99%
“…Ο συνδυασμός της α-θαλασσαιμίας και της ΔΝ έχει ως αποτέλεσμα τη χαμηλότερη ενδοκυττάρια συγκέντρωση της HbS και τον περιορισμό του πολυμερισμού της. Οι ασθενείς αυτοί παρουσιάζουν χαμηλότερα ποσοστά αιμόλυσης, υψηλότερα επίπεδα ολικής αιμοσφαιρίνης στο αίμα, χαμηλότερο μέσο όγκο ερυθρών αιμοσφαιρίων (MCV ) και ποσοστό ΔΕΚ[60,63]. Κλινικά τα ΑΕΕ, ο σπληνικός εγκλωβισμός, τα δερματικά έλκη και ο πριαπισμός περιορίζονται[64,65].…”
unclassified